ANALISIS PENINGKATAN LITERASI SAINS DENGAN PENERAPAN PEMBELAJARAN GROUP INVESTIGATION DENGAN METODE INQUIRY LABS (Universitas PGRI Sumatera Barat, 2020)
The purpose of this study was to analysis of increasing scientific literacy of the students that implement cooperative learning type GI with Inquiry Labs method. This study used two experimental classes, men and women in one of the islamic senior high school in Padang. The research method used is a weak experiment with the one group pretest-posttest design. The results showed that the scientific literacy in both classes increased and the average normalized gain <g> to a class of men is 0.30 and the class of women iss 0.43. Based on the average difference test, comparison of the increase (n-gain) students' scientific literacy of women and men did not show a significant difference for the two groups (Sig. = 0.031 <1 / 2α = 0.025). So, cooperative learning type GI with Inquiry Labs method can be applied to increase scientific literacy in the classroom both men and women classes.Keywords: Cooperative Learning Type GI, Inquiry Labs, Scientific Literacy